The Effectiveness of Guided Inquiry with SETS vision to Improve Communication Skills and Understanding of Science Concepts - Nikmah, Alfiyatun; Saptono, Sigit; Sulistyorini, Sri (Universitas Negeri Semarang, 2021)
This research aims to analyze the effectiveness of the Guided Inquiry Model with SETS (Science, Environment, Technology, and Society) vision on communication skills and understanding the concept of science. This research design is quasi-experimental design. The data were obtained from a test and the experimental report assessment rubric. The analysis data was used quantitative analysis technique i.e effect size test, N-gain test, average difference test, and simple linear regression test. The result of the effect size value of the experimental class is 1.30 in the high category, while the control class is 0.59 in the moderate category. The mean score of the students' experimental reports was higher classically in the experimental class, namely 71 and 60 in the control class. The guided inquiry learning model with SETS vision is effective in improving students' understanding of science concepts. This is indicated by the average N-gain experiment 57.80> 39.70 N-control control and the average difference test results show the value of Asymp Sig. (2-tailed) of 0,000. (0.000 <0.05). Learning that familiarizes students with scientific thinking, finding concepts and connecting concepts with everyday life and communicating their thoughts both orally and in writing trains reasoning skills. This reasoning ability can develop communication skills in students and build understanding of concepts. This study concludes that learning the SETS Vision Guided Inquiry Model is effective in improving communication skills and understanding of science concepts